International journal of handheld computing research - IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
"The International Journal of Handheld Computing Research (IJHCR) combines research from academicians and industrialists across the globe on advanced tools and technologies that perform wireless or mobile operations. Useful to scholars, researchers, and practitioners involved in related fields, this journal provides the latest developments in the theory, design, implementation, analysis, application, and standards of handheld computing."--Provided by publisher.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, issue 1 (2010); title from title screen (IGI Global, viewed Oct. 5, 2010).
Latest issue consulted: Vol. 1, issue 3 (2010).
Keywords: Computers -- Periodicals; Telecommunication -- Periodicals; Android systems; BREW systems; Browsing the mobile web; Client-side mobile commerce; Context/location-based services; Embedded systems; Energy saving; Microbrowsers; Cameras; Scanners; Data synchronization; Infrared and Bluetooth wireless communication; Batteries; Handheld devices, architecture, and systems; Handheld hardware and software integration; Handheld input and output methods and components and peripherals; Handheld specifications, standards, guidelines, software, and tools; iPhone systems; Java ME systems; Mobile advertising and sales; Mobile and wireless networks; Mobile commerce applications and systems; Mobile commerce, business, and banking; Mobile instructions and classrooms; Mobile inventory management and resource planning; Mobile messaging, emailing, broadcasting, and blogging; Mobile offices, management, and services; Mobile semantic and intelligent web; Mobile social networks and virtual communities; Mobile traffic, travel, and weather reports; Mobile Web 2.0 and plus; Mobile web and data mining; Mobile web and Internet; Mobile/handheld algorithms and methodologies; Mobile/handheld data management; Mobile/handheld entertainment and gaming; Mobile/handheld human computer interface design and implementation; Mobile/handheld operating systems and platforms; Mobile/handheld security and payment methods; Mobile/handheld/embedded database systems; Palm OS systems; Remote intranet access; Server-side mobile-commerce; Symbian systems; Windows Mobile systems; Electronic books